(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In this research, 100 female students aged from 18 to 24 years old were selected to take part in the body measurement. Data acquisition software named Imageware with a 3D scanner was employed to gain the body point-cloud diagram. Then, the characteristics of the young female lower body torso have been analyzed according to the data obtained. The regression of the key parts of women skirts and the characteristics of young female lower body torso has been found. Finally, the generating rules of the basic pattern of women skirts were established, which provides the foundation for auto-generation of skirt pattern.